Influence of Health Belief Model and Motivation with Prevention of Pulmonary Tuberculosis Transmission in Public Health Center Gurah Kediri Regency - Nanang Muhibuddin; Endah Susanti; Astri Yunita (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2021)
Tuberculosis is a health problem, both in terms of mortality or mortality, and the incidence rate of disease or morbidity. This infectious disease is mostly caused by the germ mycobacterium tuberculosis. The purpose of this study is to find out the influence of health belief models and motivation with the prevention of pulmonary tuberculosis transmission. The design used in the study is correlational analytics with a cross sectional method approach. While the sample in this study which is Some people with pulmonary tuberculosis (TB) in Gurah Health Center with BTA (+) as many as 22 respondents. The research instrument used is a questionnaire. Spearman Rhodengan test analysis of the level of significanceα=0.05, so as to be able to answer the purpose of the study. Based on Spearman Rho correlation statistical test, obtained p 0.001 result for health belief model and p 0.021, which means that the values p 0.001 and 0.021 < 0.05. From the results obtained that H1 received which means there is an influence of health belief model and motivation with the prevention of pulmonary tuberculosis transmission in Gurah Health Center Kediri Year 2020. It was concluded that the prevention of transmission of Pulmonary TB disease can be improved reciprocal relationship between health workers, families and sufferers with self-awareness of the adverse effects of Pulmonary TB disease.